ORGANIZATIONAL AND LEGAL FORMS OF SECURITY OF PUBLIC INTERESTS - Калюжний, Р. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In the article are determined the legal forms of providing of state interests. An author gives a conclusion that all of them in an organization and legal relation are directly related to functioningof state mechanism, state machine which will realize law creation, jurisdiction, law-enforcement activity accordingly with own plenary powers.